Phase I study of olaparib in combination with liposomal doxorubicin in patients with advanced solid tumours - Del Conte, G (Nature Publishing Group, 2014)
BACKGROUND: Olaparib, an oral PARP inhibitor, has shown antitumour activity as monotherapy in patients with germline BRCA1/2 (gBRCA)-mutated breast and ovarian cancer. This study evaluated olaparib capsules in combination with liposomal doxorubicin (PLD) in patients with advanced solid tumours (NCT00819221). METHODS: Patients received 28-day cycles of olaparib, continuously (days 1–28) or intermittently (days 1–7), plus PLD (40 mg m(−2), day 1); seven olaparib dose cohorts (50–400 mg bid) were explored to determine the recommended dose. Assessments included safety, pharmacokinetics, pharmacodynamics and preliminary efficacy (objective response rate (ORR)). RESULTS: Of 44 patients treated (ovarian, n=28; breast, n=13; other/unknown, n=3), two experienced dose-limiting toxicities (grade 3 stomatitis and fatal pneumonia/pneumonitis (200 mg per 28-day cycle); grade 4 thrombocytopenia (400 mg per 7-day cycle)). The maximum tolerated dose was not reached using continuous olaparib 400 mg bid plus PLD. Grade ⩾3 and serious AEs were reported for 27 (61%) and 12 (27%) patients, respectively. No major pharmacokinetic interference was observed between olaparib and PLD. The ORR was 33% (n=14 out of 42; complete response, n=3). A total of 13 responders had ovarian cancer: 10 were platinum-sensitive, 11 had a gBRCA mutation. CONCLUSIONS: Continuous/intermittent olaparib (up to 400 mg bid) combined with PLD (40 mg m(−2)) was generally tolerated and showed evidence of antitumour activity in ovarian cancer.